Bronchiolitis guidelines: what about the Italian situation in a primary care setting? - Federica Porcaro; Renato Cutrera; Anna Chiara Vittucci; Alberto Villani (Italian Journal of Pediatrics, 2023)
Abstract Acute viral bronchiolitis is the most common cause of hospitalization in children under 12 months of age. The variable clinical presentation and the potential for sudden deterioration of the clinical conditions require a close monitoring by healthcare professionals. In Italy, first access care for children is provided by primary care physicians (PCPs) who often must face to a heterogeneous disease presentation that, in some cases, make the management of patient with bronchiolitis challenging. Consequently, Italian studies report poor adherence to national and international guidelines processed to guide the clinicians in decision making in acute viral bronchiolitis. This paper aims to identify the potential factors contributing to the lack of adherence to the suggested guidelines derived by clear and evidence-based recommendations among primary care physicians operating in an outpatient setting, with a specific focus on the context of Italy. Particularly, we focus on the prescription of medications such as β2-agonists, systemic steroids, and antibiotics which are commonly prescribed by PCPs to address conditions that can mimic bronchiolitis.